Prognostic Role of Phospho-STAT3 in Patients with Cancers of the Digestive System: A Systematic Review and Meta-Analysis. - Mu-xing Li; Xin-yu Bi; Zhen Huang; Jian-jun Zhao; Yue Han; Zhi-Yu Li; Ye-fan Zhang; Yuan Li; Xiao Chen; Xu-hui Hu; Hong Zhao; Jian-qiang Cai (PLoS ONE)
Objective The definite prognostic role of p-STAT3 has not been well defined. We performed a meta-analysis evaluating the prognostic role of p-STAT3 expression in patients with digestive system cancers. Methods We searched the available articles reporting the prognostic value of p-STAT3 in patients with cancers of the digestive system, mainly including colorectal cancer, gastric cancer, hepatocellular carcinoma, esophagus cancer and pancreatic cancer. The pooled hazard ratios (HRs) with 95 % confidence intervals (95 % CIs) of overall survival (OS) and disease-free survival (DFS) were used to assess the prognostic role of p-STAT3 expression level in cancer tissues. And the association between p-STAT3 expression and clinicopathological characteristics was evaluated. Results A total of 22 studies with 3585 patients were finally enrolled in the meta-analysis. The results showed that elevated p-STAT3 expression level predicted inferior OS (HR = 1.809, 95% CI: 1.442-2.270, P < 0.001) and DFS (HR = 1.481, 95% CI: 1.028-2.133, P = 0.035) in patients with malignant cancers of the digestive system. Increased expression of p-STAT3 is significantly related with tumor cell differentiation (Odds ratio (OR) = 1.895, 95% CI: 1.364-2.632, P < 0.001) and lymph node metastases (OR = 2.108, 95% CI: 1.104-4.024, P = 0.024). Sensitivity analysis suggested that the pooled HR was stable and omitting a single study did not change the significance of the pooled HR. Funnel plots and Egger's tests revealed there was no significant publication bias in the meta-analysis. Conclusion Phospho-STAT3 might be a prognostic factor of patients with digestive system cancers. More well designed studies with adequate follow-up are needed to gain a thorough understanding of the prognostic role of p-STAT3.